Preliminary results of student survey at the University of Rome “Tor Vergata” practicing sports: a focus on the effects of Dual Career regulation - Cariati, Ida; Bonanni, Roberto; Onorati, Manuel; Tancredi, Virginia (Frontiers in Sports and Active Living, 2024)
The importance of sports and the approval of the Dual Career regulation at the University of Rome “Tor Vergata” are highly significant topics for the well-being and personal development of students. In line with European and international policies, this initiative recognizes the specific needs of student-athletes by offering them tools and flexibility to excel in both sports and academics. However, monitoring student-athletes by Universities requires thorough investigations and the development of initiatives to promote students’ adherence to sports practice. Therefore, our study aims to analyze the results of a survey administered to students enrolled at the University of Rome “Tor Vergata” during the academic years 2020/2021, 2021/2022, 2022/2023, and 2023/2024, investigating the effects of the introduction of the Dual Career regulation on the student population. Our preliminary results showed that the introduction of the Dual Career program was associated with a significant increase in the number of students practising sports over the academic years, with greater participation in the academic years 2022/2023 and 2023/2024. Noteworthy, the number of student-athletes who applied to the Dual Career program markedly increased in the last year, with the highest number of enrollments in the macroareas of Medicine and Surgery, Economy, and Engineering. Overall, the Dual Career regulation offers the possibility to plan the study path in a personalized way, dedicated academic support, and flexibility in deadlines, making the University of Rome “Tor Vergata” a model of integration between education and sportiness.